Pemanggilan Murid Secara Sengaja Berdasarkan Teladan Tuhan Yesus - Sari Saptorini (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2019)
The Lord Jesus set an example as well as a command in the ministry of making disciples. He began His ministry in this world by calling out the disciples who would be with Him and He taught specifically so that finally they could carry out the command to make disciples of all nations. Through a study of the Gospels of Matthew, Mark and Luke regarding the calling of disciples, it was found that the Lord Jesus called people intentionally and offered invitations to become His disciples. Calling to be a disciple of Jesus means a call to repentance and forgiveness of sins and to follow Him according to His purpose. He did not call people aimlessly. Therefore, in calling His disciples, the Lord Jesus also gave a vision of calling. He communicated the vision clearly so that it could be fully understood by His disciples. That vision was in line with the Great Commission given by His disciples to His ascension to heaven. As such, calling the disciples intentionally is intended to be carried out continuously by anyone who welcomes the call to be a disciple of Christ.